Searching the traces of Middle Low German in Latvian proper names - Siliņa-Piņķe, Renāte (Baltistica, 2020)
The great impact of Middle Low German on the Latvian language during the 13th–16th centuries is a well-known and rather widely researched fact. However, the main focus of linguists’ attention has so far been on the apellative vocabulary. This article therefore aims to highlight the traces of Middle Low German in Latvian proper names – placenames and personal names (both first names and surnames) – during the time of their appearance and also nowadays (also touching upon the issue of onyms that have disappeared during previous centuries). The system of Latvian personal names (as the ancient Baltic two-stem personal names gradually disappeared during the 13th–14th centuries) was largely built on the basis of Christian names in their Middle Low German versions. Among these Latvian names, borrowed from Middle Low German and still in use in the 21st century, we can note Ģederts, Indriķis, Jurģis, Tenis, Ints, Inta etc. In the context of placenames, one must take into account the historical diglossia that lasted until the 1st half of the 20th century. Between the German (initially Middle Low German) and Latvian names of cities, villages and manors there has been a diverse and manifold interaction. Meanwhile, in the names of farmhouses which were mostly coined in Latvian, one can observe many onymized borrowings from Middle Low German. The oldest Latvian surnames used in Riga during the 15th–16th centuries can sometimes be (and are) interpreted as the first documentally attested instances of some Middle Low German borrowings in the Latvian language. Among the main conclusions of this article, one can point out the fact that most Middle Low German elements have entered Latvian proper names indirectly, through borrowed common nouns. Moreover, it is essential to continue the research (especially in the field of surnames) and to reevaluate the impact of Middle Low German borrowings in the Latvian language.